Coupled thermal-hemodynamics computational modeling of cryoballoon ablation for pulmonary vein isolation. (May 2023) - Patel, Tejas; Li, Chris; Raissi, Farshad; Kassab, Ghassan S.; Gao, Tong; Lee, Lik Chuan
Abstract: Cryoballoon ablation (CBA) is a cryo-energy based minimally invasive treatment procedure for patients suffering from left atrial (LA) fibrillation. Although this technique has proved to be effective, it is prone to reoccurrences and some serious thermal complications. Also, the factors affecting thermal distribution at the pulmonary vein-antrum junction that are critical to the treatment success is poorly understood. Computer modeling of CBA can resolve this issue and help understand the factors affecting this treatment. To do so, however, numerical challenges associated with the simulation of advection-dominant transport process must be resolved. Here, we describe the development of a thermal-hemodynamics computational framework to simulate incomplete occlusion in a patient-specific LA geometry during CBA. The modeling framework uses the finite element method to predict hemodynamics, thermal distribution, and lesion formation during CBA. An incremental pressure correction scheme is used to decouple velocity and pressure in the Navier-Stokes equation, whereas several stabilization techniques are also applied to overcome numerical instabilities. The framework was implemented using an open-source FE library (FEniCS). We show that model predictions of the hemodynamics in a realistic human LA geometry match well with measurements. The effects of cryoballoon position, pulmonary vein blood velocity and mitral regurgitation on lesion formation during CBA was investigated. For a − 70 0 C cryoballoon temperature, the model predicts lesion formation for gaps less than 2.5 mm and increasing efficiency of CBA for higher balloon tissue contact areas. The simulations also predict that lesion formation is not sensitive to variation in pulmonary vein blood velocity and mitral regurgitation. The framework can be applied to optimize CBA in patients for future clinical studies. Graphical abstract: Image 1 Highlights: Novel thermal hemodynamics computational model to simulate cryoballoon ablation. Developed stabilized finite element method in FEniCS for patient specific modeling. Validations with clinical measurements are presented for left atrium flow dynamics. Effect of cryoballoon position, pulmonary vein velocity on lesion is investigated.